Clinical Utility of Circulating Tumor Cells in ALK-Positive Non-Small-Cell Lung Cancer - Faugeroux, Vincent; Pailler, Emma; Auger, Nathalie; Taylor, Melissa; Farace, Françoise (Frontiers in Oncology, 2014)
The advent of rationally targeted therapies such as small-molecule tyrosine kinase inhibitors (TKIs) has considerably transformed the therapeutic management of a subset of patients with non-small cell lung cancer (NSCLC) harboring defined molecular abnormalities. When such genetic molecular alterations are detected the use of specific TKI has demonstrated better results (overall response rate (ORR), progression free survival (PFS)) compared to systemic therapy. However the detection of such molecular abnormalities is complicated by the difficulty in obtaining sufficient tumor material, in terms of quantity and quality, from a biopsy. Here we described how circulating tumor cells (CTCs) can have a clinical utility in ALK (anaplastic lymphoma kinase) positive NSCLC patients to diagnose ALK-EML4 gene rearrangement and to guide therapeutic management of these patients. The ability to detect genetic abnormalities such ALK rearrangement in CTCs shows that these cells could offer new perspectives both for the diagnosis and the monitoring of ALK-positive patients eligible for treatment with ALK inhibitors.